14-3-3 proteins contribute to leaf and root development via brassinosteroid insensitive 1 in Arabidopsis thaliana - Lee, Jae Hoon; Kwak, Geunhwa; Lim, Yong Pyo; Oh, Man-Ho (Genes & genomics, 2020)
Background Brassinosteroids (BR) are essential growth hormone in plants. Various components involved in signal transduction pathway have been identified as targets of 14-3-3 phospho-binding proteins. Previously, we showed that 14-3-3 proteins directly interact with the Brassinosteroid Insensitive 1 (BRI1), the BR receptor kinase, and are also subject to phosphorylation in a BR-dependent manner. Objective In this study, we aimed to examine a potential interplay between 14-3-3 proteins and BRI1 in plant growth. Methods Morphological phenotypes of a T-DNA insertion mutant line, 14 - 3 - 3ψφε , defective in three 14-3-3 isoforms, psi, phi and epsilon, were characterized and compared with bri1 - 5 and two transgenic lines for BRI1, BRI1-Flag and BRI1-Flag ( 14 - 3 - 3ψφε ). We also generated complementation lines carrying each of the three 14-3-3 genes and determined their differences in rosette growth. Results No significant differences between the wild-type and 14 - 3 - 3ψφε seedlings were observed regardless of BR applications. However, BRI1-Flag ( 14 - 3 - 3ψφε ) showed a significantly reduced cold tolerance and BR sensitivity in hypocotyl and root development when compared to BRI1-Flag. In addition, narrower leaf shape and smaller rosette size were observed in BRI1-Flag ( 14 - 3 - 3ψφε ), while the mutant phenotypes were partially restored in the complementation lines, two of which with 14 - 3 - 3φ and 14 - 3 - 3ε showed the rosette growth comparable to BRI1-Flag. Conclusion Taken together, our results suggested that 14-3-3 proteins might positively regulate BRI1 activity and showed that 14-3-3 isoforms have different functional impacts in BR signaling.